Composite Materials: Fatigue and Fracture: Fifth Volume 1995
DOI: 10.1520/stp14030s
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Realistic Ply-Drop Geometries on Interlaminar Stresses in Tapered Laminates

Abstract: A finite element model of a tapered specimen was developed that incorporates naturally occurring realistic geometries such as ill-formed resin pockets, unsymmetric and offset ply-drop locations, varying ply thickness, and voids. Parametric studies were performed to determine the effects of these geometries, which occur naturally in a manufactured specimen. Illformed resin pockets increase the effective taper angle at the ply drop and cause a corresponding increase in the interlaminar stresses. In addition, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…As expected, experiments have shown that, in most cases, delaminations at interfaces such as between the terminated and continuous plies are the typical mode of damage, although other types of damages, such as matrix cracking and fiber breakage, have been observed [5,7,8]. The majority of the previous work on stress analyses of laminates with ply drop-offs has been accomplished through the use of the finite element methods, e.g., [2,7,9]. These analyzes have shown that stress concentrations occur in the region where the plies are dropped off.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…As expected, experiments have shown that, in most cases, delaminations at interfaces such as between the terminated and continuous plies are the typical mode of damage, although other types of damages, such as matrix cracking and fiber breakage, have been observed [5,7,8]. The majority of the previous work on stress analyses of laminates with ply drop-offs has been accomplished through the use of the finite element methods, e.g., [2,7,9]. These analyzes have shown that stress concentrations occur in the region where the plies are dropped off.…”
mentioning
confidence: 74%
“…Delaminations not only decrease the load-carrying capability of the structure, but can also lead to other types of damage that induce premature failure. Such being the case, many researchers have investigated laminates with ply drop-offs, both experimentally and analytically, e.g., [3][4][5][6][7][8][9]. As expected, experiments have shown that, in most cases, delaminations at interfaces such as between the terminated and continuous plies are the typical mode of damage, although other types of damages, such as matrix cracking and fiber breakage, have been observed [5,7,8].…”
mentioning
confidence: 99%
“…Vizzini and Shukla had the discontinuous plies cut to achieve a taper ratio of approximately 10:1, resulting in a taper angle of 5.71∞. Even at this taper ratio, the resin pockets were most likely at a taper ratio of 5:1 [6]. The discontinuous plies for the current research were cut to fit as close to the inclusion edge as possible, meaning that the taper angle was limited by the drape characteristics of the uncured prepreg.…”
Section: Quasistatic Loadingmentioning
confidence: 99%
“…The first group investigated the various parameters influencing the properties of tapered composite structures. These parameters include: ply drop location, laminate thickness, number of plies dropped at one location, fabric type, loading condition, fiber content, and spacing between ply drops [2][3][4][5][6][7][8]. The other group focused on identifying failure mechanisms associated with tapered composite structures.…”
Section: Introductionmentioning
confidence: 99%